Mixed-severity natural disturbance regime dominates in an old-growth Norway spruce forest of northwest Russia - Khakimulina, Tatiana; Fraver, Shawn; Drobyshev, Igor (2016)
Questions: What were the long-term disturbance rates (including variability) and agents in pristine Norway spruce-dominated (Picea abies (L.) Karst.) forests? Have soil moisture conditions influenced disturbance rates across this boreal spruce-dominated forest? Were the temporal recruitment patterns of canopy dominants associated with past disturbance periods? Location: Interfluvial region of Northern Dvina and Pinega rivers, Arkhangelsk, northwest Russia. Methods: We linked dendrochronological data with tree spatial data (n trees=1659) to reconstruct the temporal and spatial patterns of canopy gaps in a 1.8-ha area from 1831-2008, and to develop a growth-release chronology from 1775-2008. Results: No evidence of stand-replacing disturbances was found within selected forest stands over the studied period. Forest dynamics were driven by small- to moderate-scale canopy disturbances, which maintained a multi-cohort age structure. Disturbance peaks were observed in the 1820s, 1920s, 1970s and 2000s, with decadal rates reaching 32% of the stand area disturbed. Conclusions: The overall mean decadal rate was 8.3% canopy area disturbed, which suggests a canopy turnover time of 122yr, with a 95% confidence envelop of 91-186yr. Bark beetle outbreaks (possibly exacerbated by droughts) and wind-storms emerged as the principal disturbance agents. Recruitment of both Norway spruce and downy birch was associated with periods of increased canopy disturbance. Moisture conditions (moist vs mesic stands) were not significantly related to long-term disturbance rates. The studied spruce-dominated boreal forests of this region apparently exhibited long-term forest continuity under this mixed-severity disturbance regime. These disturbances caused considerable structural alterations to forest canopies, but apparently did not result in a pronounced successional shifts in tree species composition, rather occasional minor enrichments of birch in these heavily spruce-dominated stands.